Rho-GTPase Activating Protein myosin MYO9A identified as a novel candidate gene for monogenic focal segmental glomerulosclerosis. - Li, Qi; Gulati, Ashima; Lemaire, Mathieu; Nottoli, Timothy; Bale, Allen; Tufro, Alda (Kidney Int, 2021)
Focal segmental glomerulosclerosis (FSGS) is a podocytopathy leading to kidney failure, whose molecular cause frequently remains unresolved. Here, we describe a rare MYO9A loss of function nonsense heterozygous mutation (p.Arg701) as a possible contributor to disease in a sibling pair with familial FSGS/proteinuria. MYO9A variants of uncertain significance were identified by whole exome sequencing in a cohort of 94 biopsy proven patients with FSGS. MYO9A is an unconventional myosin with a Rho-GAP domain that controls epithelial cell junction assembly, crosslinks and bundles actin and deactivates the small GTPase protein encoded by the RHOA gene. RhoA activity is associated with cytoskeleton regulation of actin stress fiber formation and actomyosin contractility. Myo9A was detected in mouse and human podocytes in vitro and in vivo. Knockin mice carrying the p.Arg701MYO9A (Myo9A) generated by gene editing developed proteinuria, podocyte effacement and FSGS. Kidneys and podocytes from Myo9A mutant mice revealed Myo9A haploinsufficiency, increased RhoA activity, decreased Myo9A-actin-calmodulin interaction, impaired podocyte attachment and migration. Our results indicate that Myo9A is a novel component of the podocyte cytoskeletal apparatus that regulates RhoA activity and podocyte function. Thus, Myo9A knock-in mice recapitulate the proband FSGS phenotype, demonstrate that p.R701X Myo9A is an FSGS-causing mutation in mice and suggest that heterozygous loss-of-function MYO9A mutations may cause a novel form of human autosomal dominant FSGS. Hence, identification of MYO9A pathogenic variants in additional individuals with familial or sporadic FSGS is needed to ascertain the gene contribution to disease.

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology. - Vilarinho, Sílvia; Choi, Murim; Jain, Dhanpat; Malhotra, Ajay; Kulkarni, Sanjay; Pashankar, Dinesh; Phatak, Uma; Patel, Mohini; Bale, Allen; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (J Hepatol, 2014)
BACKGROUND & AIMS: In children with liver failure, as many as half remain of indeterminate aetiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbour known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate aetiology. METHODS: Patient 1 was a 10 year-old female diagnosed with Wilson disease but no detectable ATP7B mutations, and decompensated liver cirrhosis who underwent liver transplant and subsequently developed onset of neurodegenerative disease. Patient 2 was a full-term 2 day-old male with fatal acute liver failure of indeterminate aetiology. Patient 3 was an 8 year-old female with progressive syndromic cholestasis of unknown aetiology since age 3 months. RESULTS: Unbiased whole-exome sequencing of germline DNA revealed homozygous mutations in MPV17 and SERAC1 as the disease causing genes in patient 1 and 2, respectively. This is the first demonstration of SERAC1 loss-of-function associated fatal acute liver failure. Patient 1 expands the phenotypic spectrum of the MPV17-related hepatocerebral mitochondrial DNA depletion syndrome. Patient 3 was found to have syndromic cholestasis due to bi-allelic NOTCH2 mutations. CONCLUSIONS: Our findings validate the application of whole-exome sequencing in the diagnosis and management of children with advanced liver disease of indeterminate aetiology, with the potential to enhance optimal selection of treatment options and adequate counselling of families. Moreover, whole-exome sequencing revealed a hitherto unrecognized phenotypic spectrum of inherited metabolic liver diseases.
Keywords: Amino Acid Sequence; Base Sequence; Carboxylic Ester Hydrolases; Child; Cholestasis; DNA Mutational Analysis; End Stage Liver Disease; Exome; Fatal Outcome; Female; Genes, Recessive; Hepatolenticular Degeneration; Heterozygote; Homozygote; Humans; Infant, Newborn; Liver Failure; Liver Failure, Acute; Male; Membrane Proteins; Mitochondrial Proteins; Molecular Sequence Data; Pedigree; Receptor, Notch2; RNA Splice Sites; Sequence Homology, Amino Acid